An atomtronic experimental setup for engineering quantised circulations - Gan, Koon Siang (Nanyang Technological University, 2022)
The growing field of Atomtronics is an important frontier for fundamental research and the development of new quantum technologies. Atomtronics is the study of atomic systems analogous to electronic circuits and components, where the carriers are neutral atoms instead of electrons. The dynamics of these simulated systems are useful for quantum metrology, magnetic sensing, rotational sensing and even to simulate black holes. Experimental Atomtronic setups thus require great flexibility and precision to manipulate the parameters of the system. A suitable candidate is an alkali atom Bose-Einstein Condensate as its superfluid property is useful to generate persistent currents. Persistent currents in ring structures play an important role in Atomtronics as it forms the basis of many interesting Atomtronic systems such as ring lattices and stacked rings. Conventional methods of generating a circulation is via optical stirring or by imparting Orbital Angular Momentum(OAM). However, these methods could be inadequate with the increased complexity of Atomtronic systems. Hence, a novel method for generating circulations is proposed and numerically simulated in this thesis. This method was inspired by two separate experiments, where it was shown that independent condensates in a segmented ring can create circulation through random phase acquisition, and a phase gradient imprint can reliably generate 1 angular momentum in a ring condensate. Bringing both ideas together, a novel protocol is devised where a 6 segment ring is imprinted with a set of phases. A total of three methods of phase imprinting were simulated. The initial two methods determined the successful set of phases, and the required imprint time. The final imprint method followed experimental methods and used previous results to show that circulations of up to winding number 2 can be created. In order to test this protocol, an Atomtronic experiment setup which produced a Rubidium-87 Bose-Einstein Condensate(BEC) was constructed. The atom cloud is initially condensed in a far-detuned optical crossed dipole trap, but is subsequently transferred to a combined blue-detuned optical trap. It is composed of two independent 532nm traps which provide strong vertical confinement to study 2D physics, and lateral trapping that can create highly tunable arbitrary traps. The capability of this setup is demonstrated by loading the condensate into a few arbitrary traps. Matter-wave interference is performed through a dynamic splitting of a square condensate, which shows the capability of our experimental setup. In the near future, this BEC setup will be used to perform the simulated novel circulation protocol and also ring lattice potentials.